2018
DOI: 10.1002/jcb.27956
|View full text |Cite
|
Sign up to set email alerts
|

The role of IL‐3 in bone

Abstract: In the recent past, there has been a burgeoning interest in targeting cytokines such as IL‐3 for specific disease conditions of bone such as rheumatoid arthritis and multiple myeloma. Unlike other cytokines, IL‐3 is a cytokine with a multilineage potential and broad spectrum of target cells and it plays a vital role in hematopoiesis. Due to its common receptor subunit, the action of IL‐3 shows functional redundancy with other cytokines such as the granulocyte‐macrophage colony‐stimulating factor and IL‐5. IL‐3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
(172 reference statements)
0
3
0
Order By: Relevance
“…Through this signaling pathway, IL-3 promotes basophil growth and differentiation, which are involved in allergic rhinitis. 27,28 Additionally, IL-3 has strong hematopoietic effects, promoting the production of granulocytes, monocytes, mast cells, basophils, and macrophages, which could also promote airway inflammation 29 in response to air pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Through this signaling pathway, IL-3 promotes basophil growth and differentiation, which are involved in allergic rhinitis. 27,28 Additionally, IL-3 has strong hematopoietic effects, promoting the production of granulocytes, monocytes, mast cells, basophils, and macrophages, which could also promote airway inflammation 29 in response to air pollution.…”
Section: Discussionmentioning
confidence: 99%
“…IL-3, also known as multicolony stimulation factor (multi-CSF), is a member of the βc family due to the fact that its receptor shares the signaling subunit βc with granulocyte/macrophage colony-stimulating factor (GM-CSF) and IL-5 ( 134 ). Activated T lymphocytes, mast cells, and osteoblasts are the primary secretors ( 135 ).…”
Section: Interleukinsmentioning
confidence: 99%
“…IL-1-has been shown to induce OC survival by acting through the PI 3-kinase/Akt and ERK signaling pathways and by reducing caspase-3 activity (Lee et al, 2002). It has been shown that OCPs and mature OCs express IL-3R which is necessary for OCP survival and commitment to OC lineage, whereas its role in OC differentiation has not been fully delineated yet (Soysa and Alles, 2018). IL-6 is a known activator of OC bone resorption activity.…”
Section: Interleukins (Ils)mentioning
confidence: 99%